Analisis I-HDI (Islamic-Human Development Index) di Jawa Timur - Maya Masita Septiarini; Sri Herianingrum (Universitas Airlangga, 2017)
This research aims to analyze the human development achievement in East Java in 2010-2014 which is measured based on islamic-human development index. This research also compares towards the human development achievement based on HDI (Human Development Index) and I-HDI. The research method used in this research is descriptive qualitative with 11 secondary data from BPS/Central Statistic Body and two calculation data from I-HDI. The result from the calculation of I-HDI shows that the majority of cities kota/regencies in East Java during 2010-2014 were in mid end to low end category, with relatively far disparity among regencies/cities. Meanwhile, from the result of calculation of HDI, mostly the human development achievement in East Java were in mid end to high end category. This explains that I-HDI is more comprehensive in measuring the human development achievement compared to I-HDI.